Assessing cross-country inequalities in global burden of gastrointestinal cancers: slope and concentration index approach - Haoyun Zhou; Yongbo Wang; Fang Wang; Runtang Meng; Yong Yu; Su Han; Yu Zhang; Yu Wu; Xiaoxue Liu (Discover Oncology)
Abstract Purpose New cases and deaths of gastrointestinal cancers are predicted to increase significantly by 2040. This study aims to explore cross-country inequalities and trends in global burdens of colon and rectum cancer (CRC), esophageal cancer (EC) and gastric cancer (GC). Methods Data from the Global Burden of Diseases Study 2019 were analyzed to examine trends in disability-adjusted life-years (DALYs) for three gastrointestinal cancers with estimated annual percentage change (EAPC) and Joinpoint analysis. Inequality in their DALYs rates was assessed with the slope index of inequality and the concentration index, based on the Socio-Demographic Index (SDI). Results From 1990 to 2019, the age standardized DALYs rate of CRC decreased in these countries from high and high-middle SDI regions, with the EAPC values of − 1.018% and − 0.161%, respectively, but increased among low, low-middle and middle SDI regions (EAPC = 1.035%, 0.926% and 0.406%, respectively). The age standardized DALYs rates of EC and GC decreased in all SDI regions. Moreover, the slope index changed from 358.42 (95% confidence interval 343.28 to 370.49) to 245.13 (217.47 to 271.24) for CRC, from − 63.88 (− 87.48 to − 48.28) to − 1.36 (− 32.44 to 25.87) for EC, and from 126.37 (101.97 to 146.47) to 58.04 (20.54 to 96.12) for GC. The concentration index for CRC moved from 29.56 (28.99 to 29.84) to 23.90 (23.19 to 24.26), from − 9.47 (− 10.30 to − 9.24) to − 14.64 (− 15.35 to − 14.24) for EC, and from 8.44 (7.85 to 8.72) to − 6.42 (− 7.65 to − 6.12) for GC. Conclusion This study suggests strong heterogeneity in global DALYs for gastrointestinal cancers across different SDI regions. Higher SDI regions faced a greater burden of CRC, while the burdens of EC and GC were more prevalent in lower SDI regions.